Glutamate in Salience Network Predicts BOLD Response in Default Mode Network During Salience Processing - von Düring, Felicia; Ristow, Inka; Li, Meng; Denzel, Dominik; Colic, Lejla; Demenescu, Liliana Ramona; Li, Shijia; Borchardt, Viola; Liebe, Thomas; Vogel, Matthias; Walter, Martin (Frontiers in Behavioral Neuroscience, 2019)
Background Brain investigations identified salience network (SN) comprising the dorsal Anterior Cingulate Cortex (dACC) and the Anterior Insula (AI). Magnetic resonance spectroscopy (MRS) studies revealed the link between the glutamate concentration in the ACC and alterations in attentional scope. Hence, we investigated whether glutamate concentration in the dACC modulates brain response during salience processing. Methods Twenty-seven healthy subjects (12♀, 15♁) provided both STEAM MRS at 7T measuring glutamate concentrations in the dACC as well as a functional magnetic resonance imaging (fMRI) task to study the influence on content-related salience processing and expectedness. Salience was modulated for both sexual and non-sexual emotional photos in either expected or unexpected situations. Correlation between MRS and task fMRI was investigated by performing regression analyses controlling for age, gender, and gray matter partial volume. Results/Conclusion During picture processing, the extent of deactivation in the Posterior Cingulate Cortex (PCC) was attenuated by two different salience attributions: sexual content and unexpectedness of emotional content. Our results indicate that stimulus inherent salience induces an attenuation of the deactivation in PCC, which is in turn balanced by higher level of glutamate in the dACC.